Well-Being and Innovation: Investigating the Linkage among Well-Being Oriented Management, Knowledge Sharing, Innovation Climate, and Innovative Work Behavior - Tegar Satya Putra; Aloysia Desy Pramusiwi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
For businesses to survive, innovation is essential. As a result, business experts and academics engaged in extensive discussions about encouraging creativity in corporate settings. However, most of the present literature focuses on the performance management paradigm when discussing innovation. Innovation is a resource-intensive process that, while it improves corporate performance, drains employees' resources. Thus, evaluating innovation through more critical lenses is needed. Through the lenses of the Theory of Conservation of Resources and Job Demand Resources Model, this research views innovation as a job demand and well-being oriented management as human resource intervention to enhance employee well-being. This intervention provides additional resources for employees to conduct innovation through knowledge sharing and is moderated by innovation climate. Purposive sampling is employed for this research survey and yields 150 valid responses. The data is then analyzed using SEM-PLS. The result shows that well-being oriented management positively influences knowledge sharing, and knowledge sharing positively influences innovative work behavior. Furthermore, knowledge sharing is also proven to mediate between well-being-oriented management and innovative work behavior. Moreover, innovation climate does not moderate the relationship between knowledge sharing and innovative work behavior. The result implies that managers must uphold their staff members' well-being by employing well-being-oriented management.